EFFECTS OF PULMONARY REHABILITATION ON PULMONARY INFLAMMATION IN INDIVIDUALS WITH SEVERE ASTHMA (CIPEEX, 2025)
Introduction: Asthma is a chronic inflammatory disease of the airways, with high prevalence in Brazil, affecting quality of life and potentially leading to frequent hospitalizations. Severe asthma, a more complex condition, requires intensive treatment and is associated with changes in airway microbiota. Non-pharmacological strategies, such as aerobic training (AT), have shown benefits, including improved physical capacity and reduced airway inflammation. Recently, kinins, inflammatory mediators, have been identified as potential agents in asthma, contributing to bronchoconstriction and increased vascular permeability. Objective: To assess whether pulmonary rehabilitation modulates levels and expression of kinins, kinogens, and pro-inflammatory cytokines in the lungs of patients with severe asthma. Methodology: The study will recruit 100 patients with severe asthma, aged 18-59 years, randomized into two groups: Control and Rehabilitation. The training will include aerobic and resistance exercises, as well as inspiratory muscle training. Pre- and post-rehabilitation assessments will be conducted, including asthma control, quality of life, and levels of cytokines and kinins in exhaled breath condensate and induced sputum. Data will be statistically analyzed to determine the effects of the training on the modulation of inflammatory mediators and improvement in symptoms of severe asthma. Expected Results: It is anticipated that pulmonary rehabilitation will lead to a reduction in systemic pro-inflammatory cytokines, including Th1, Th2, and Th17 cytokines, as well as a decrease in plasma levels of kinins and kinogens.
Keywords: severe asthma; rehabilitation; pumonary inflamation